2017
DOI: 10.1016/j.maturitas.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone, follicle stimulating hormone, antral follicle count, and risk of menopause within 5 years

Abstract: Objective To evaluate the ability of concentration of anti-Müllerian hormone (AMH), antral follicle count (AFC), and concentration of follicle stimulating hormone (FSH) to predict the onset of menopause. Study Design The Coronary Artery Risk Development in Young Adults Study (CARDIA) Women’s Study was an ancillary study to CARDIA, a population-based study of adults aged 18–30 years followed for 3 decades. For this report, participants were women (n=426) who had attended the CARDIA year 15–16 (2000–2001) exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…Several indicators can be used to assess ovarian reserve function, including FSH, inhibin B, AMH and AFC. The data in this study revealed that AMH and AFC were superior to menstrual cycles and FSH in evaluating ovarian function in older women, which is consistent with the results reported in most previous research [16][17]. As a woman ages, her oocyte and follicular pool declines, so AFC is a good indicator of ovarian function in women.…”
Section: Discussionsupporting
confidence: 91%
“…Several indicators can be used to assess ovarian reserve function, including FSH, inhibin B, AMH and AFC. The data in this study revealed that AMH and AFC were superior to menstrual cycles and FSH in evaluating ovarian function in older women, which is consistent with the results reported in most previous research [16][17]. As a woman ages, her oocyte and follicular pool declines, so AFC is a good indicator of ovarian function in women.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study reported that serum AMH is superior to antral follicle count (AFC) and FSH in improving the predictive ability of the onset of menopause in combination with age . However, the population‐based cohort study with over 3000 females participants revealed that the low intraclass correlation coefficient for AMH trajectories of time to menopause (0.32) do not support the uniform AMH decline trajectory.…”
Section: General Populationmentioning
confidence: 99%
“…There is an increased likelihood for a healthy woman to reach menopause before the median age of 51 years if AMH is low for her age [ 49 ]. Conversely, if her AMH level is more than 0.02 ng/ml (0.14 pmol/l), there is minimal chance of menopause within 5 years regardless of women's age [ 50 ]. The application of a low AMH to predict the probability of menopause is more sensitive in late than in young reproductive age women, but an undetectable AMH level (using a high-sensitivity assay) is predictive of menopause within 5 years in only 60% of healthy women aged more than 45 years [ 50 ].…”
Section: Introductionmentioning
confidence: 99%